2023
DOI: 10.1001/jamanetworkopen.2023.8655
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Propylthiouracil vs Methimazole for Thyroid Storm in Critically Ill Patients

Abstract: ImportanceThyroid storm is the most severe form of thyrotoxicosis, with high mortality, and is treated with propylthiouracil and methimazole. Some guidelines recommend propylthiouracil over methimazole, although the difference in outcomes associated with each treatment is unclear.ObjectiveTo compare outcomes associated with use of propylthiouracil vs methimazole for the treatment of thyroid storm.Design, Setting, and ParticipantsThis comparative effectiveness study comprised a large, multicenter, US-based coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Although both drugs decrease thyroid hormone synthesis, US guidelines recommend propylthiouracil for patients with thyroid storm because unlike methimazole, propylthiouracil blocks T 4 to T 3 conversion . However, a recent comparative effectiveness study found no difference in in-hospital mortality, costs, adverse events, or duration of organ support among those treated with propylthiouracil compared with methimazole . In addition to lowering serum T 3 levels, patients should be treated in the intensive care unit and any precipitating illness should be addressed .…”
Section: Methodsmentioning
confidence: 99%
“…Although both drugs decrease thyroid hormone synthesis, US guidelines recommend propylthiouracil for patients with thyroid storm because unlike methimazole, propylthiouracil blocks T 4 to T 3 conversion . However, a recent comparative effectiveness study found no difference in in-hospital mortality, costs, adverse events, or duration of organ support among those treated with propylthiouracil compared with methimazole . In addition to lowering serum T 3 levels, patients should be treated in the intensive care unit and any precipitating illness should be addressed .…”
Section: Methodsmentioning
confidence: 99%
“…MMI may be given orally at a dose of 20 mg every 6 h if PTU is contraindicated. Notably, findings from a recent large observational study support interchangeable use of these medications [ 58 ]. Intravenous and rectal administration of thioamides has also been described [ 59 62 ].…”
Section: Managementmentioning
confidence: 99%
“…The thyroid storm is a rare but potentially fatal condition. Only a few studies have been conducted to test the efficacy and safety of specific pharmacological treatments in thyroid storm with confusing results [ 34 ]. The literature review shows anecdotal cases and sporadic experiences [ 35 37 ] or case series [ 38 ] managed in emergency circumstances during intensive care with severe cases of thyrotoxicosis accompanied by hemodynamic decompensation and marked alteration of the level of consciousness (coma).…”
Section: Evidence On the Use Of Perchlorates In Hyperthyroidism And T...mentioning
confidence: 99%